2017
DOI: 10.3847/1538-3881/aa832a
|View full text |Cite
|
Sign up to set email alerts
|

The Transiting Multi-planet System HD 3167: A 5.7 M Super-Earth and an 8.3 M Mini-Neptune

Abstract: HD 3167 is a bright (V = 8.9 mag) K0 V star observed by NASA's K2 space mission during its Campaign8. It has recently been found to host two small transiting planets, namely, HD 3167b, an ultra-short-period (0.96 days) superEarth, and HD 3167c, a mini-Neptune on a relatively long-period orbit (29.85 days). Here we present an intensive radial velocity (RV) follow-up of HD 3167 performed with the FIES@NOT, HARPS@ESO-3.6 m, and HARPS-N@TNG spectrographs. We revise the system parameters and determine radii, masse… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
55
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 79 publications
(59 citation statements)
references
References 89 publications
4
55
0
Order By: Relevance
“…Notably, the three complementary methods all yielded the same conclusions, resulting in a mass measurement for the innermost planet that is not only precise but also robust. Demory et al 2011Demory et al , 2016Winn et al 2011;Nelson et al 2014), CoRoT-7b (Léger et al 2009;Queloz et al 2009;Haywood et al 2014), WASP-47e (Becker et al 2015;Dai et al 2015;Sinukoff et al 2017b;Vanderburg et al 2017), Kepler-78b (Howard et al 2013;Pepe et al 2013;Sanchis-Ojeda et al 2013;Hatzes 2014;Grunblatt et al 2015), Kepler-10b (Batalha et al 2011;Dumusque et al 2014;Weiss et al 2016;Rajpaul et al 2017), K2-131b , HD 3167b (Vanderburg et al 2016a;Christiansen et al 2017;Gandolfi et al 2017, respectively labeled as C17 and G17 in the plot), K2-106b (Guenther et al 2017;Sinukoff et al 2017a, G17 and S17 respectively). Notably, the last two planets have two independent density measurements that are not consistent with each other, resulting in a disagreement in the interpretation of the internal composition.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, the three complementary methods all yielded the same conclusions, resulting in a mass measurement for the innermost planet that is not only precise but also robust. Demory et al 2011Demory et al , 2016Winn et al 2011;Nelson et al 2014), CoRoT-7b (Léger et al 2009;Queloz et al 2009;Haywood et al 2014), WASP-47e (Becker et al 2015;Dai et al 2015;Sinukoff et al 2017b;Vanderburg et al 2017), Kepler-78b (Howard et al 2013;Pepe et al 2013;Sanchis-Ojeda et al 2013;Hatzes 2014;Grunblatt et al 2015), Kepler-10b (Batalha et al 2011;Dumusque et al 2014;Weiss et al 2016;Rajpaul et al 2017), K2-131b , HD 3167b (Vanderburg et al 2016a;Christiansen et al 2017;Gandolfi et al 2017, respectively labeled as C17 and G17 in the plot), K2-106b (Guenther et al 2017;Sinukoff et al 2017a, G17 and S17 respectively). Notably, the last two planets have two independent density measurements that are not consistent with each other, resulting in a disagreement in the interpretation of the internal composition.…”
Section: Discussionmentioning
confidence: 99%
“…These planets have the advantage that due to their short periods, their masses and radii can be determined with high accuracy. Currently known transiting ultrashort-period planets (USPs) include CoRoT-7b (Léger et al 2009), 55 Cnc e (Winn et al 2011), Kepler-10b (Batalha et al 2011), Kepler-78b (Sanchis-Ojeda et al 2013, WASP-47e (Dai et al 2015;Sinukoff et al 2017a), KOI 1843.03 ), K2-106 (Guenther et al 2017), and HD3167b (discovery: Vanderburg (2016), characterization: Gandolfi et al (2017)).…”
Section: Introductionmentioning
confidence: 99%
“…Other potentially interesting objects to search for the signatures of volcanism and an exosphere using optical transmission spectroscopy are K2-106 (Guenther et al 2017) and HD3167 b (Vanderburg 2016;Gandolfi et al 2017;Christiansen et al 2017). What makes these objects interesting is that their densities are higher than that of 55 Cnc e. K2-106 b and HD3167 b have a density of 13.1 −3.6 +5.4 and 8.00 +1.10 −0.98 g cm −3 , respectively.…”
Section: Introductionmentioning
confidence: 99%
“…We used the coadded FIES spectrum, which has an SNR ratio of ∼150 per pixel at 5500 Å, to derive the fundamental parameters of GJ9827. The analysis was performed following the procedures already adopted for other K2 host stars (Johnson et al 2016;Barragán et al 2017b;Fridlund et al 2017;Gandolfi et al 2017;Guenther et al 2017). We took advantage of four different spectral analysis packages applied independently by different subgroups within our team.…”
Section: Spectroscopic Observationsmentioning
confidence: 99%
“…Sinukoff et al (2016) reported the detection of 11 multiplanetary systems from K2 Campaigns 1 and 2. However, there are few such systems around nearby stars (Armstrong et al 2015;Crossfield et al 2015;Gandolfi et al 2017), and only a handful around brighter stars that are suitable for spectroscopic characterization.…”
Section: Introductionmentioning
confidence: 99%